Social-based Guidance and Self-adaptivity within Enrolment Processes - Ajanovski, Vangel (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University - Skopje, Macedonia, 2013)
This paper introduced new dynamic scenarios for better management of the activities related to the term enrolment process within a university student information system, and present a model solution where the students will be making better choices with regard to the length of studies and accomplishing the right set of skills for the right degree and specialization, while at the same time optimally using resources. In the first part of the paper an introduction is made and the necessity of such system is explained together with the positioning of the solution within the student interests and the time-frame with regard to the processes of term enrolment and class timetable scheduling. The last part of the paper discusses the way in which the earlier introduced virtual academic adviser can be used to perform the proposed integrated scenario for term enrolment and class schedule within an overall self-adaptive framework that controls the behaviour of the system actively and automatically and only requests action from the involved participants when needed.